2018
DOI: 10.1016/j.compositesb.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of interlaminar and intralaminar damages in laminated composites under indentation loading using Acoustic Emission

Abstract: This study focuses on the clustering of the indentation-induced interlaminar and intralaminar damages in carbon/epoxy laminated composites using Acoustic Emission (AE) technique. Two quasi-isotropic specimens with layups of [60/0/-60] 4S (is named dispersed specimen) and [60 4 /0 4 /-60 4 ] S (is named blocked specimen) were fabricated and subjected to a quasi-static indentation loading. The mechanical data, digital camera and ultrasonic C-scan images of the damaged specimens showed different damage evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(68 citation statements)
references
References 43 publications
2
65
1
Order By: Relevance
“…In our previous research [32], the performance of six different clustering methods to classify the AE signals of interlaminar and intralaminar damage mechanisms in specimens S D and S B under quasistatic indentation loading is compared and finally, three damage mechanisms containing matrix cracking, fiber breakage and delamination were clustered using the hierarchical model. The clustered AE data of these damage mechanisms is shown in Fig.…”
Section: Quasi-static Indentation Testmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous research [32], the performance of six different clustering methods to classify the AE signals of interlaminar and intralaminar damage mechanisms in specimens S D and S B under quasistatic indentation loading is compared and finally, three damage mechanisms containing matrix cracking, fiber breakage and delamination were clustered using the hierarchical model. The clustered AE data of these damage mechanisms is shown in Fig.…”
Section: Quasi-static Indentation Testmentioning
confidence: 99%
“…This fact shows that there Table 5). As can be seen, despite the dynamic and quasi-static nature of LVI and indentation tests and also the utilized method (clustering indentation AE data by hierarchical model [32] and analyzing impact data by WPT) there is a good consistency between the percentage of different damage mechanisms for LVI and indentation tests that it shows AE is a powerful tool to…”
Section: Low-velocity Impact Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, the initial matrix crack AE activities at load cycles LC3 and LC4 illustrate the fact that matrix crack has an unstable evolution behavior in these load cycles. However, due to the fact that matrix cracking is not usually considered as a critical damage mode individually [18], this point is not considered as the critical damage state of the plate. At the initial stage of load cycle LC5, some delamination AE activities are found that show the unstable behavior of delamination growth for this load cycle.…”
Section: Critical Damage Detection By Aementioning
confidence: 99%
“…These studies almost focused on two subjects; 1) Damage detection and classification, and 2) Damage localization. Saeedifar et al [17,18] employed AE to detect, classify and also trace the evolution of different damage mechanisms in CFRP plates under quasi-static indentation and LVI loading conditions. There are different approaches to localize damage in a composite plate using AE such as triangulation [19,20], delta T-mapping [21,22], multi-steps and optimizing techniques [23], etc.…”
Section: Introductionmentioning
confidence: 99%